Sexualitet, samtycke och relationer i grundskolans bildämne - Elisabeth Lisa Öhman (Utbildning & Demokrati)
Sexuality, Consent and Relationships in Swedish Arts Education. The aim of this study is to examine how the knowledge area of sexuality, consent and relationships could come into being in the context of Swedish Arts education. More specifically, it explores how phenomena such as identity, sexuality, and gender are material—discursively produced during 15–16-year-old students’ work with photographic portraits in Arts education in Grade 9. Using Karen Barad’s concept of space-time-matter in the analysis shows how subject-didactic opportunities and challenges reformulate the ideas about what sexuality education can be. Results also show how the notions of sexuality, consent and relationships are transformed in the open-ended process of working with Arts education as a material-discursive entanglement.